2016
DOI: 10.1186/s40795-016-0077-3
|View full text |Cite
|
Sign up to set email alerts
|

Dietary diversity and related factors among lactating women visiting public health facilities in Aksum town, Tigray, Northern Ethiopia

Abstract: Background: Dietary diversity is a proxy indicator of maternal nutrient adequacy. However, little is documented on dietary diversity among lactating mothers. Therefore, this study assessed diet diversity and associated factors among lactating mothers visiting public health facilities in Aksum town, Tigray, Northern Ethiopia. Methods: An institution based cross-sectional study was conducted on 346 randomly selected lactating women visiting public health facilities of Aksum town in June 2015. Dietary diversity w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
72
8
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(93 citation statements)
references
References 23 publications
12
72
8
1
Order By: Relevance
“…27 Furthermore, many studies in developing countries have documented that their dietary sources are mainly cereal based. 28 Pregnant women who were using protected water as a main source were 12.5 times more likely to have a diversified diet than those who were using unprotected water as the main source. This result is supported by different studies.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…27 Furthermore, many studies in developing countries have documented that their dietary sources are mainly cereal based. 28 Pregnant women who were using protected water as a main source were 12.5 times more likely to have a diversified diet than those who were using unprotected water as the main source. This result is supported by different studies.…”
Section: Discussionmentioning
confidence: 97%
“…This study is supported by studies conducted in Ethiopia which revealed that home gardening was strongly associated with diet diversity and with frequency of vegetable consumption. 22,29 This might be due to the reason that households with gardens benefited because they are able to diversify their daily food. It has been shown elsewhere that parents with home gardens grow vegetables to obtain additional diet options that enhance the diversity of the household's food sources.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, factors like monthly income, not having home gardening, and a source of drinking water from the protected well was the determinate to have low dietary diversity. 15 The mean±standard deviation (SD) of DDS of lactating mothers was 4.9±1.9 respectively and the magnitude of high DDS and underweight was 32.8% and 40.6%resepectively. This show that underweight was associated with lactating women's dietary diversity score and poor feeding practice.…”
Section: Introductionmentioning
confidence: 96%
“…During pregnancy and lactation, women are more vulnerable to undernutrition than others at reproductive age, due to increased energy and nutrient requirements [5,6,7]. Globally in 2011, the prevalence of anemia in pregnant women was 38.2% vs. 29% in non-pregnant women [8].…”
Section: Introductionmentioning
confidence: 99%